Characterization of physiological races of Phytophthora infestans (Mont.) de Bary in lulo (Solanum quitoense Lam.) - Zapata P., José Luis; Bernal E., Jorge A. (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2019)
Lulo blight is one of the most important problems of this crop in Colombia, present in all departments of the country that grow it, with an incidence of 100%. Due to the ignorance of the complexity of physiological races of Phytophthora infestans in cultivated lulo (Solanum quitoense), collections were evaluated from potato (Solanum tuberosum sub species andigena), tree tomato (Cyphomandra betacea) , tomato (Solanum lycopersicum) and water cucumber or sweet cucumber (Solanum muricatum) obtained in various lulo producing departments of Colombia. The results obtained on the virulence of the pathogen on 11 potato differentials (along with the variety Tuquerreña) indicated that for lulo there are 15 physiological races with, according to octal nomenclature, 4211 being the most frequent with 23.25% frequency and virulence factors of 0, 4, 8 and 11, collected in the municipalities of Rionegro and Urrao, followed by 2211, 0213, 0231 and 1112 with four virulence factors and a frequency of 2.32% each, collected in the municipalities Oporapa, Jardín, Jardín and Santa Rosa de Cabal, respectively. Similarly, we found 3223 with virulence factors 1, 2, 4, 7, 10, and 11 in potato, 4421 with factors 0, 3, 7, 10 and 11 collected from the tomato and 4000 with virulence factor 0 in cucumber; indicating that the pathogen from potato is the most complex.